Pembentukan Desa Mitra Santun Lansia di Desa Tunas Mudo Sekernan Ilir Muaro Jambi - Ernawati Ernawati; Loriza Sativa Yan (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2023)
Advances in the health sector affected to the quality of all aspects of life including health services for the elderly. The ageing process in the elderly reduced their independence in maintaining health and independence in carrying out daily activities. The elderly were also very vulnerable to non-communicable diseases such as heart failure, hypertension, stroke and diabetes. Elderly people in the community can be empowered in terms of health education, screening for health risk factors and maintaining physical exercise. One of the strategies to increase the participation of the elderly’s provided elderly-friendly areas in a sustainable manner. This activity is the development of a partner village with the concept of an elderly-friendly village in Tunas Mudo Village, the Working Area of the Sekernan Ilir Muaro Jambi Health Center, which was carried out from July to September 2022. In the early stages of the activity, coordination was established with the Head of the Public Health Center and the local Village Head, then socialization was carried out with cadres, villagers and the elderly. At the implementation stage, there are 3 activities of screening and exercise for the elderly. This community service activity results investigated the health volunteer knowledge that was slightly increased for identifying changes in the elderly and maintaining the health of the elderly, the participation of the elderly in screening activities and physical exercise was improved. Supervision should be carried out routinely so that the elderly and villagers are able to implement friendly health behavior for the elderly and reduce risk factors for non-communicable diseases in the elderly